PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA PADA GEOMETRI KELAS V SD - Rita Puspita Puspita; Agus Susanta; Irwan Koto (UNIB Press, 2022)
The study aims to develop Students’ Worksheets (LKPD) by using Problem Based Learning Method assisted Geogebra that is feasible, practical and interesting. In this study, researchers used the ADDIE development model with five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Only four stages are imposed on teachers and fifth grade students of SD Negeri 2 Pendopo. The result of the research is thestudents’ worksheets by using Problem Based Learning Method assisted Geogebra on the material of volume building which is valid based on expert judgment on three aspects of; feasibility. material feasibility with 0.88 validity, language feasibility with 0.88 validity, and media feasibility 0.77, students’ responses 0.92, and positive responses from the teachers. The result indicated that students’ worksheets by using Problem Based Learning Method assisted Geogebra is feasible and received a very positive response.